2018
DOI: 10.1371/journal.pone.0192704
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitor PD-1 pathway is down-regulated in synovium at various stages of rheumatoid arthritis disease progression

Abstract: Immune checkpoint blockade with therapeutic anti-cytotoxic T lymphocyte-associated antigen (CTLA)-4 (Ipilimumab) and anti-programmed death (PD)-1 (Nivolumab and Pembrolizumab) antibodies alone or in combination has shown remarkable efficacy in multiple cancer types, concomitant with immune-related adverse events, including arthralgia and inflammatory arthritis (IA) in some patients. Herein, using Nivolumab (anti-PD-1 antagonist)-responsive genes along with transcriptomics of synovial tissue from multiple stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 38 publications
5
97
1
1
Order By: Relevance
“…We also observed that in several patients with inflammatory arthritis, inflammatory symptoms persisted after discontinuation of ICI therapy, which is largely unique to Rh‐irAEs . Patients with RA have exhibited increased expression of PD‐1 in synovial tissue , suggesting one potential mechanistic pathway whereby ICIs may induce disease flares or reveal preclinical RA .…”
Section: Discussionmentioning
confidence: 63%
“…We also observed that in several patients with inflammatory arthritis, inflammatory symptoms persisted after discontinuation of ICI therapy, which is largely unique to Rh‐irAEs . Patients with RA have exhibited increased expression of PD‐1 in synovial tissue , suggesting one potential mechanistic pathway whereby ICIs may induce disease flares or reveal preclinical RA .…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, in this study we found that MSC treatment led to increased PD-1 expression in T reg after short-and long-term evaluation, which may contribute to the protective effects of MSC on gut inflammation. The interaction of these surface molecules has been reported as important factor that attenuates the inflammatory response in autoimmune diseases [63]. Conversely, GITR is constitutively expressed by T reg and upon exposure to alloantigens [62].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, PD-1 is expressed by activated T and B cells [45]. Of interest, transcripts of the co-inhibitory PD-L1 ligand are highly expressed in RA synovium, but expression of PD-L1 protein appears to be blocked by serum soluble (s)PD-L1, which is present at high levels in seropositive RA, thereby downregulating the PD-1/PD-L1 inhibitory signalling axis [47]. Of interest, transcripts of the co-inhibitory PD-L1 ligand are highly expressed in RA synovium, but expression of PD-L1 protein appears to be blocked by serum soluble (s)PD-L1, which is present at high levels in seropositive RA, thereby downregulating the PD-1/PD-L1 inhibitory signalling axis [47].…”
Section: Dcs As Master Orchestrators Of Immune Responsesmentioning
confidence: 99%